2009
DOI: 10.1159/000218361
|View full text |Cite
|
Sign up to set email alerts
|

Sound Localization and Binaural Hearing in Children with a Hearing Aid and a Cochlear Implant

Abstract: The aims of the study were to investigate whether sound localization acuity improved when children with 1 cochlear implant use a hearing aid in the contralateral ear (bimodal fitting), and whether this enabled them to benefit from a binaural masking level difference. Four different noise bursts were used as stimuli for a minimal audible angle localization test. On average, localization acuity remained poor with the cochlear implant alone, but also with bimodal fitting. A significant benefit of bimodal fitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…To date, there are no MAA studies examining a large number of healthy children at different ages and within a wide range of acoustic space. The available small database already shows a trend for the continuous development of spatial hearing; in an unpublished Dutch study [cited in Beijen et al, 2010], 14 participants with normal hearing (6-19 years) showed an average MAA threshold of 10° for 500-ms broadband-noise pulses (0.3-7 kHz) presented either from the left or from the right side while abstaining from the use of reference signals at 0°. Related to the presently used measurement method (3-AFC), this corresponds to an MAA threshold of 5°.…”
Section: Auditory Spatial Discrimination Undergoes Continuous Developmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there are no MAA studies examining a large number of healthy children at different ages and within a wide range of acoustic space. The available small database already shows a trend for the continuous development of spatial hearing; in an unpublished Dutch study [cited in Beijen et al, 2010], 14 participants with normal hearing (6-19 years) showed an average MAA threshold of 10° for 500-ms broadband-noise pulses (0.3-7 kHz) presented either from the left or from the right side while abstaining from the use of reference signals at 0°. Related to the presently used measurement method (3-AFC), this corresponds to an MAA threshold of 5°.…”
Section: Auditory Spatial Discrimination Undergoes Continuous Developmentioning
confidence: 99%
“…To date, published data mostly refer to the spatial hearing abilities of adults [Makous and Middlebrooks, 1990;Perrott and Saberi, 1990;Middlebrooks and Green, 1991;Blauert, 1997;Sabin et al, 2005]. Respective data for children are rather sparse, and were mostly collected as mere comparative data for studies on children with hearing impairments or cochlear implants [Bess et al, 1986;Beijen et al, 2010]. Infants have also been studied, and in these studies -because of the limited ability of infants to cooperate in behavioral studies requiring voluntary decisionsstimulus-induced head/eye movements were used to indicate the detection of a shift in sound source location.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…'Binaural squelch' refers to a range of central auditory processing mechanisms which improve the effective SNR by analysing differences in the phase and level of the signal arriving at each ear. Neither adult, nor child users of BMS are able to fully utilise binaural squelch mechanisms as current speech processing strategies are unable to reliably code phase information required for the perception of interaural timing and phase differences [7,23]. The 'head shadow effect' is caused by interactions between the acoustic signal and the head which result in between-ear differences in the SNR at each ear.…”
Section: Speech Recognitionmentioning
confidence: 99%